Macrophage subpopulations in pediatric patients with lupus nephritis and other inflammatory diseases affecting the kidney. - Sandersfeld, Mira; Büttner-Herold, Maike; Ferrazzi, Fulvia; Amann, Kerstin Ute; Benz, Kerstin; Daniel, Christoph (Arthritis Research & Therapy, 2024)
BACKGROUND: Macrophages play an important role in the pathogenesis of lupus nephritis (LN), but less is known about macrophage subtypes in pediatric LN. Here we compared renal inflammation in LN with other inflammatory pediatric kidney diseases and assessed whether inflammation correlates with clinical parameters. METHODS: Using immunofluorescence microscopy, we analyzed renal biopsies from 20 pediatric patients with lupus nephritis (ISN/RPS classes II-V) and pediatric controls with other inflammatory kidney diseases for infiltration with M1-like (CD68 + /CD206 - , CD68 + /CD163 -), M2a-like (CD206 + /CD68 +), and M2c-like macrophages (CD163 + /CD68 +) as well as CD3 + T-cells, CD20 + B-cells, and MPO + neutrophilic granulocytes. In addition, the correlation of macrophage infiltration with clinical parameters at the time of renal biopsy, e.g., eGFR and serum urea, was investigated. Macrophage subpopulations were compared with data from a former study of adult LN patients. RESULTS: The frequency of different macrophage subtypes in biopsies of pediatric LN was dependent on ISN/RPS class and showed the most pronounced M1-like macrophage infiltration in patients with LN class IV, whereas M2c-like macrophages were most abundant in class III and IV. Interestingly, on average, only half as many macrophages were found in renal biopsies of pediatric LN compared to adult patients with LN. The distribution of frequencies of macrophage subpopulations, however, was different for CD68 + CD206 + (M2a-like) but comparable for CD68 + CD163 - (M1-like) CD68 + CD163 + (M2c-like) cells in pediatric and adult patients. Compared to other inflammatory kidney diseases in children, fewer macrophages and other inflammatory cells were found in kidney biopsies of LN. Depending on the disease, the frequency of individual immune cell types varied, but we were unable to confirm disease-specific inflammatory signatures in our study due to the small number of pediatric cases. Worsened renal function, measured as elevated serum urea and decreased eGFR, correlated particularly strongly with the number of CD68 + /CD163 - M1-like macrophages and CD20 + B cells in pediatric inflammatory kidney disease. CONCLUSION: Although M1-like macrophages play a greater role in pediatric LN patients than in adult LN patients, M2-like macrophages appear to be key players and are more abundant in other pediatric inflammatory kidney diseases compared to LN.
EVALuna2:552742